PENGARUH LAMA STERILISASI TERHADAP MUTU SAYUR LEBUI KALENG: Effect Of Sterilization Time On Quality Of Pigeon Pea Soup - Adella Putrinita; Baiq Rien Handayani; moegiratul amaro (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2022)
Sayur lebui or pigeon pea soup is a traditional Lombok that has been used plastic as a packaging. Plastic packaging has a weakness in the presence of monomers and small molecules that will migrate into food, making the shelf life relatively low with high microbial contamination. One technology that can be used to overcome this is canning technology. The most important process in canning is the sterilization process. This study aims to determine the effect of sterilization time on the quality of canned lebui vegetables. The method used in this study was an experimental method carried out in the laboratory. The design used in this study was a randomized block design (RBD) with a single factor experiment, namely the duration of sterilization with 6 treatments, namely 0 minute, 3 minutes, 6 minutes, 9 minutes, 12 minutes, 15 minutes. Analyzed using ANOVA with a significant level of 5% using Co-stat software. The difference data was tested using Honestly Significant Differences (HSD) Test. The prolonged sterilization treatment of pigeon pea soup had a significant effect on the pH value, antioxidant activity, color, organoleptic parameters of texture, color and appearance, but had no significant effect on the organoleptic parameters of aroma and taste. Based on chemical, physical and organoleptic parameters, sterilization time of 9 minutes is recommended to produce the best pigeon pea soup with an antioxidant activity value of 86.05%, a pH value of 5.03, an oHue value of 45.27 (red) and hedonic organoleptic quality and a score that is still acceptable.